Src: Marker or Actor in Prostate Cancer Aggressiveness - Vlaeminck-Guillem, Virginie; Gillet, Germain; Rimokh, Ruth (Frontiers in Oncology, 2014)
A key question for urologic practitioners is whether an apparently organ-confined prostate cancer is actually aggressive or not. The dilemma is to specifically identify among all prostate tumors the very aggressive high-grade cancers that will become life-threatening by developing extra-prostatic invasion and metastatic potential and the indolent cancers that will never modify a patient’s life expectancy. A choice must be made between several therapeutic options to achieve the optimal personalized management of the disease that causes as little harm as possible to patients. Reliable clinical, biological or pathological markers that would enable distinctions to be made between aggressive and indolen prostate cancers in routine practice at the time of initial diagnosis are still lacking. The molecular mechanisms that explain why a prostate cancer is aggressive or not are also poorly understood. Among the potential markers and/or actors in prostate cancer aggressiveness, Src and other members of the Src kinase family, are valuable candidates. Activation of Src-dependent intracellular pathways is frequently observed in prostate cancer. Indeed, Src is at the cross-roads of several pathways (including androgen receptor, TGFbeta, Bcl-2, Akt/PTEN or MAPK and ERK …), and is now known to influence some of the cellular and tissular events that accompany tumor progression: cell proliferation, cell motility, invasion, epithelial-to-mesenchymal transition, resistance to apoptosis, angiogenesis, neuroendocrine differentiation, and metastatic spread. Recent work even suggests that Src could also play a part in prostate cancer initiation in coordination with the androgen receptor. The aim of this review is to gather data that explores the links between the Src kinase family and prostate cancer progression and aggressiveness.